IMPLIKASI TEORI BUNGA TERHADAP MANAJEMEN KEUANGAN DALAM PERSPEKTIF EKONOMI ISLAM - M. Nuruddin Umar; Mohammad Naim Musafik; Arisyahidin Arisyahidin (Universitas Islam Kadiri, 2020)
This study aimed to describe the implications of the theory of interest to financial management. Results of the description viewed from the standpoint of Islamic economics. The implication variable that really stood out are theory of interest; interest philosophy, the concept of interest and usury, the concept of money, the concept of time value of money and the economic value of time, the concept of cost of capital, and interest as a revenue. The variables in financial management implicated by of the theory interest are the general economic, investment, pricing, inflation and money supply, economic growth, unemployment, social welfare and exchange rate. This study is a literature research (library research), which is using books as a source of data to explain the issues studied. The character of this study is descriptive qualitative research that describe and analyze the data clearly on the theories of interest and their implications to financial management on the Islamic economics perspective. Source of data used in this research is secondary data, ie data obtained from the study of literature in the form of analysis of books, papers and websites. According to the type of data that is required of the study, the data analysis technique used is the technique of